SIMBOLISASI DAN REPRESENTASI BUDAYA PATRIARKI DALAM MANUSKRIP JAWA: TINJAUAN SEMIOTIKA CHARLES SANDERS PIERCE - Setyawan, Bagus Wahyu; Teguh (Widya Aksara : Jurnal Agama Hindu, 2024)
Patriarchal culture has been deeply rooted and shackled in almost all aspects of people's social life. Even literary works are also influenced by a very strong patriarchal culture. This research aims to reveal the symbolization and representation of patriarchal culture in Javanese manuscripts. The selected data source is Javanese manuscripts aimed specifically at women, namely Serat Wulangreh Putri, Serat Candrarini, and Serat Wulang Wanita. The data collection technique uses content analysis techniques and hermeneutic readings of the three manuscripts. The data analysis in this study uses Charles Sanders Pierce's semiotic theory with the concept of reading three-meaning semoticons. The results found in this study are that there are several forms of depictions of patriarchal culture in the three manuscripts that make the roles and positions of Javanese women marginalized. The impact of patriarchal cultural hegemony is the existence of subordination, the emergence of double burdens, and psychological violence against women. In these manuscripts, there is also a recommendation that women must accept the practice of polygamy carried out by their husbands. Thus, it is necessary to take a step of reconciliation and reinterpretation to form a new perspective in responding to duties and women in the family. It is appropriate for husband and wife to establish good communication and a proportionate division of roles in the family so as not to be influenced by patriarchal understanding.